Politik Anggaran Pendidikan yang Minus Keberpihakan - FATHUR JSP RAHMAN (Jurnal Studi Pemerintahan, 2011)
This study is about the politics of pro-poor budget. Pro-poor budget is the budget set out in APDNrelated to the policy on the poor. The observed object is political education budget in the budget of theSemarang City, 2009. The results of this study, suggests that the education sector budget in the 2009Budget, the Semarang City, there is no statement showing the pro-poor. Although the education sectorbudget increased to 35 percent of the entire budget. But in reality, its implementation is not up to thelevel of transparency and accountability are ineffective and inefficient. Causes of non-affirmativeeducation sector budget policy in the 2009 Budget of Semarang is a structural factor. Hence, the needsof the poor should be the main target of budget allocations in the education sector in order to liberatethe poor from poverty.Keywords: Pro poor budgeting,